1985
DOI: 10.1139/t85-077
|View full text |Cite
|
Sign up to set email alerts
|

Back analysis of the Nerlerk berm liquefaction slides

Abstract: Five liquefaction slides occurred in 1983 during the construction of a hydraulically placed subsea sand berm designed to form part of a bottom-founded, offshore, hydrocarbon exploration platform at Nerlerk in the Canadian Beaufort Sea. These slides were triggered by simple static loading arising from the sand placement itself. Failures started at locally oversteepened side slopes and retrogressed to form bowl-shaped crests. The slide material came to rest beyond the berm at very flat slopes. Stability back ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 3 publications
4
37
0
2
Order By: Relevance
“…Instability and loss of controllability took place much sooner for the looser sand specimen than for the denser one. Similar findings have been experimentally produced by Sladen et al [8], Sasitharan et al [45], di Prisco and Imposimato [49] and Gajo et al [50], and numerically verified by Wan et al [51] using Gudehus' probe tests at several stress states along a conventional triaxial loading path under drained conditions.…”
Section: Constant Shear (Q-constant) Testssupporting
confidence: 86%
See 1 more Smart Citation
“…Instability and loss of controllability took place much sooner for the looser sand specimen than for the denser one. Similar findings have been experimentally produced by Sladen et al [8], Sasitharan et al [45], di Prisco and Imposimato [49] and Gajo et al [50], and numerically verified by Wan et al [51] using Gudehus' probe tests at several stress states along a conventional triaxial loading path under drained conditions.…”
Section: Constant Shear (Q-constant) Testssupporting
confidence: 86%
“…Notable instances of this are natural landslides in very shallow angled soil slopes, [7][8][9] and the collapse of a loose sand when sheared under undrained conditions or mixed stress-strain control [10,11]. In the latter, after reaching a peak-stress ratio far away from the plastic limit surface, the loose sand succumbs to a spontaneous loss in strength in the absence of any localized deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of fines contents on the liquefaction resistance of sand-fines composite material previously reported are summarized as: -fines have little or no effect on liquefaction resistance (Ishihara 1993), -fines increase liquefaction (Chang et al 1982;Kuerbis et al 1988;Yasuda et al 1994), (Troncoso and Verdugo 1985;Sladen et al 1985;Vaid 1994), and -fines reduce liquefaction resistance until a certain threshold in fines content, and then increase liquefaction resistance (Koester 1994;Lade and Yamamuro 1997).…”
Section: Testing Methodsmentioning
confidence: 99%
“…Several researchers have related instability conditions to the state parameter (Sladen et al, 1985;Anderson & Riemer, 1995;Yang, 2002). However, as observed by Chu et al (2003) and Wanatowski et al (2010), the state parameter concept may not be used directly for prediction of the instability behaviour of sand.…”
Section: Soil Statementioning
confidence: 99%
“…The possibility of static liquefaction or instability occurring for dilating sand has also been observed in several case studies. In a discussion to identify the mechanisms that caused the failure of the Nerlerk berm in the Canadian Beaufort Sea (Sladen et al, 1985), Been et al (1987) concluded that the failure could have occurred for dilatant sand. Several other cases of flow slide failure in dilatant sand have also been presented by Been et al (1988).…”
Section: Introductionmentioning
confidence: 99%